Post Percutaneous Coronary Intervention Outcomes Related to the Renal Seromarkers of Contrast-Induced Nephropathy Patients with Acute Coronary Syndrome (Bangladesh Journal of Infectious Diseases, 2025)
Background: Urinary albumin excretion is recognized as an early marker of renal dysfunction and has been associated with adverse renal outcomes following percutaneous coronary intervention in patients with acute coronary syndrome.Objective: The purpose of this present study was to assess the development of contrast-induced nephropathy among patients with acute coronary syndrome undergoing percutaneous coronary intervention.Methodology: This cross-sectional analytical study was conducted in the Department of Cardiology at the National Heart Foundation Hospital and Research Institute (NHFH & RI), Dhaka, from August 2021 to July 2023. A total of 164 consecutive acute coronary syndrome patients undergoing percutaneous coronary intervention were enrolled and categorized into two groups based on urinary albumin excretion: microalbuminuria and normoalbuminuria. Microalbuminuria (MA) was defined as a urinary albumin-to-creatinine ratio (uACR) of 30–300 mg/g in a random spot urine sample. The relationship between pre-procedural microalbuminuria and the occurrence of contrast-induced nephropathy was further assessed using receiver operating characteristic (ROC) curve analysis.Results: Among the 164 patients, 67 (41%) had microalbuminuria and 97 (59%) had normoalbuminuria. The mean uACR was significantly higher in the microalbuminuria group (73.75 ± 5.6 mg/g) compared to the normoalbuminuria group (16.24 ± 6.43 mg/g). contrast-induced nephropathy developed in 24 patients (36%) in the microalbuminuria group, whereas only 15 patients (16%) in the normoalbuminuria group experienced contrast-induced nephropathy. ROC curve analysis identified a uACR threshold of 223.17 mg/g as the optimal cut-off for predicting contrast-induced nephropathy, with the best balance of sensitivity and specificity.Conclusion: In conclusion, pre-procedural microalbuminuria is significantly associated with an increased risk of contrast-induced nephropathy in acute coronary syndrome patients undergoing percutaneous coronary intervention.Bangladesh Journal of Infectious Diseases, June 2025;12(1):134-140